VERBAL COMUNICATION - Aminjonova Durdona Ravshanjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article discusses the picture of the current state of the theory of verbal and non-verbal communication. The connection between verbal and non-verbal means of communication is analyzed.